Uji Cemaran Mikroba Dalam Susu Kedelai Tanpa Merek Di Kecamatan Jaya Baru Kota Banda Aceh Secara Total Plate Count (TPC) - Yuni Dewi Safrida; Raihanaton Raihanaton; Ananda Ananda (Jurnal Serambi Engineering, 2019)
Soy Milk is white-yellow liquid or kind of beverage that produced by home Industry which should shown about its quality and hygienic to prevented from microba. The purpose of this research is to find out the level of Microba contamination from No-Brand Soy Milk that sold in Jaya Baru Banda Aceh. This research conducted in May 7 th – 12 th 2018 at AKAFARMA Laboratory, Banda Aceh. The sample was No-Brand Soy Milk that taken from six different places and analyzed by using Random Sampling. It was a descriptive research and using TPC as the method. The result shown that first LT TPC was 23×106 colony/ml, second E was 49×106 colony/ml, third LD was 86×106 colony/ml, forth B was 28×107 colony/ml, fifth LB was 26×106 colony/ml and the last PBC was 50×105 colony/ml, it can be conclude that the sixth-samples of Soy  Milk that sold In Jaya Baru, Banda Aceh were not eligible to SNI   tandard, No.06.8-7388-2009 that has 5×104 colony/ml as its TPC toward the Soy Milk extrac.